BS EN IEC 62841-2-19 AMD1. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 2-19. Particular requirements for hand-held jointers (4th February 2022) - British Standards Institution,
No abstract available